KAJIAN KENYAMANAN THERMAL PADA BANGUNAN RUMAH TINGGAL ARSITEKTUR KOLONIAL MODERN (Studi Kasus : Rumah Tinggal Karya Arsitek Liem Bwan Tjie Jl. Dr. Wahidin No. 38 Semarang) - Setyohadi KP, RM. Bambang (Semarang State University, 2011)
Residential building located on the street Dr. Wahidin No. 38 Semarang is the architectural artifacts that remain. The building was founded in 1938 by architect Liem Bwan Tjie modern colonial-style architecture. In architectural design, the climate is a major consideration, the climate in a region and a desire to meet the demands of convenience must produce a physical design solution design.